Penerapan Latihan Lompat Gawang Berbantuan Bola Gantung terhadap Hasil Ketepatan Smash Bola Voli pada Ekstrakurikuler - Suita, I Gede; Pandra, Viktor; Syafutra, Wawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the significant improvement in the hanging ball-assisted hurdle training on the volleyball smash accuracy results in extracurricular activities at Ciptodadi Junior High School, Musi Rawas Regency. The research method used in this study was a pre-experimental design. The study's results showed that the pre-test yielded an average value of 16.8, and the post-test an average value of 22.15. The results of the normality test obtained x^2 count < x^2 table (1.3121 < 4.95), thus the data were normally distributed. The results of the t-test calculation yielded a Z count (7.2) greater than the Z table value (2.09) at a 5% significance level. This means that H0 is rejected and Ha is accepted. In other words, the hypothesis proposed in this study can be accepted as accurate. The conclusion is that implementing hanging ball-assisted hurdle training can significantly improve volleyball smash accuracy in extracurricular activities at Ciptodadi Junior High School, Musi Rawas Regency. Keywords: Hanging Ball, Goal Jump, Volleyball Smash